Los costos y su relación con el estado de producción y ventas de queso fresco en la empresa Novillo del cantón Pujilí, Provincia de Cotopaxi, año 2013 - Cunalata Guato, Daisy Mirella (2014)
For all industrial company it is important that their productive process is good, for it is needed it that these they are clear and be managed appropriately based that necessity was carried out this investigation work where it was determined the production costs and its relationship with the State of Costs of Production and sales of fresh cheese in the company “NOVILLO” of the Canton Pujilí, County of Cotopaxi, year 2013, for that determination or classification was necessary to apply so much different methods of investigation like of costs. Among the methods that this the direct observation was used because he went necessary to go to the place where the facts are given to get the necessary information and to be able to continue with the outlined topic, others of the used methods are the inductive, analytic and other necessary since our work is based more on the calculation. These calculations are carried out low methods of the theory of costs proposed by authors of books……